THE MAIN PRINCIPLES, GOALS AND TASKS OF MODERN ENTERPRISE MANAGEMENT - Dadajonova Martabo Makhmudovna (Scholar Express Journals, 2023)
In the article, the main principles of enterprise management, goals and tasks are thoroughly analyzed, and the means and methods of achieving efficiency in management are clearly defined.
Keywords: Efficiency; managerial; strategic